Method for preparing lithium slag-based molecular sieve by eutectic salt-assisted melting of lithium slag
The method of preparing lithium slag-based molecular sieve through eutectic salt-assisted molten lithium slag is solved, and the problems of high alkali melting temperature and high energy consumption in the preparation process of lithium slag in the prior art are achieved, and high-efficiency and low-cost high-value utilization of lithium slag is achieved.
Patent Information
- Application Number
- CN202510137542.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-02-07
AI Technical Summary
The existing methods for preparing molecular sieves for lithium slag have problems such as high alkali melting temperature, large energy consumption, and many impurities, making it difficult to achieve efficient and low-cost high-value utilization of lithium slag.
The method of preparing lithium slag-based molecular sieve is adopted to prepare eutectic salt-assisted molten lithium slag. Through the pretreatment, alkali melting, maturation and crystallization steps, the alkali melting temperature is reduced, the molecular sieve yield is improved, and energy consumption is reduced.
It realizes efficient preparation of lithium slag, reduces energy consumption, improves the purity and utilization of molecular sieves, and promotes the high-value utilization of lithium slag.
Smart Images

Figure CN119569077B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of molecular sieves, and in particular to a method for preparing lithium slag-based molecular sieves with the assistance of eutectic salt-assisted melting of lithium slag. Background Art
[0002] With the adjustment of energy structure and the rapid development of new energy vehicles, smart electronic devices, energy storage and other industries, lithium carbonate is in great demand as the core raw material of lithium batteries. However, according to the existing different production processes, every ton of lithium carbonate produced will result in the production of 8 to 30 tons of lithium slag. As industrial solid waste, the stock of lithium slag has reached 1.2 billion tons in my country alone, and the output is growing rapidly at an annual rate of 12 million tons. Except for a small amount of lithium slag (<10%) used in construction projects, most of them are treated by open-air stacking or landfilling. The stockpile volume remains high and increases year by year, which will not only cause a waste of land resources, but also the residual sulfides and harmful substances will pose a potential threat to the environment that cannot be ignored.
[0003] Lithium slag is mainly composed of oxides such as silicon and aluminum. It has high activity and can be used as an admixture for cement and concrete to improve and adjust the performance of cement or concrete. However, the comprehensive utilization of lithium slag still has problems such as low utilization rate and low product added value. For example, as an auxiliary cementitious material, its amorphous active matter participating in the reaction accounts for only 30%, and the utilization rate is not high. In addition, the utilization of lithium slag lacks relevant national industry standards and specifications, and there are policy risks, which has led to many cement, building materials and other companies restricting the addition of lithium slag as an admixture. At the same time, the newly revised national standard "General Portland Cement" (GB175-2023) also further restricts the use of lithium slag as a cement admixture. Therefore, the development of high-value utilization of lithium slag is the primary way to solve its disposal problem and create economic value.
[0004] Since the main components in lithium slag are similar to molecular sieves, there are studies on replacing chemical raw materials with lithium slag to prepare molecular sieves, thereby realizing high-value utilization. The proposed methods are mainly divided into two categories: the first category is lithium slag aqueous alkali dissolution: when lithium slag is dissolved in an alkaline solution, components such as SiO2 and Al2O3 therein will dissolve and enter the liquid phase to form a silicate solution, and then form a molecular sieve through hydrothermal crystallization. The dissolution rate of lithium slag in alkaline solution is slow, and there are problems such as long dissolution time, low efficiency, and incomplete dissolution. For example, patent CN113548673A provides a method for preparing molecular sieves using lithium slag, which mainly shortens the alkali dissolution time by using high frequency and high power ultrasound when lithium slag is dissolved. The second category is high-temperature alkali melting of lithium slag: through the action of high temperature and alkali flux, the chemical bonds in the lithium slag are broken and the crystal structure is destroyed, the originally ordered crystal structure becomes disordered, and the reactivity of lithium slag is improved. Compared with the aqueous alkali dissolution of lithium slag, the high-temperature alkali fusion of lithium slag has a more complete reaction, higher efficiency and shorter time. However, the alkali fusion temperature is at least above 300°C (201811610136.9, 201911137814.9, 202410132283.9), and there are problems such as high reaction temperature, high energy consumption and high cost. For example, patent CN101624191A discloses a method for preparing 13X molecular sieve using lithium slag as raw material, and 13X molecular sieve is prepared by high-temperature alkali fusion, aging and crystallization. When the alkali fusion temperature or the alkali fusion time is reduced, the prepared molecular sieve has more impurity phases. Summary of the invention
[0005] In view of the problems of the prior art, the present invention provides a method for preparing lithium slag-based molecular sieves by eutectic salt-assisted melting of lithium slag. Two or more salts form the eutectic molten salt, which can reduce the alkali melting temperature, increase the molecular sieve yield, and reduce energy consumption.
[0006] The technical solution of the present invention is as follows:
[0007] The present invention provides a method for preparing a lithium slag-based molecular sieve by eutectic salt-assisted melting of lithium slag, comprising the following steps:
[0008] (1) Acid pretreatment: The lithium slag raw material is subjected to acid pretreatment to obtain pretreated lithium slag;
[0009] (2) Alkali melting: Grind and mix the pretreated lithium slag with eutectic salt evenly, and react at 200-350°C for 2-6 hours to obtain eutectic lithium slag;
[0010] (3) Ripening: Add the eutectic lithium slag into water, stir and react for 0.5 to 2 hours, and then ultrasonicate for 0.5 to 1 hour to obtain a mixed solution containing silicon and aluminum compounds;
[0011] (4) Crystallization: crystallize the mixed solution containing silicon-aluminum compounds at 80-140°C for 6-24 hours, separate the solid and liquid after the reaction, wash the solid to neutrality, and dry it to obtain a lithium slag-based molecular sieve;
[0012] The eutectic salt includes an alkali flux and an auxiliary salt, the alkali flux is sodium hydroxide, and the auxiliary salt is at least one of chloride, fluoride, carbonate, sulfate, and nitrate; the molar ratio of the alkali flux to the auxiliary salt is 4-19:1.
[0013] The auxiliary salt of the present invention includes, but is not limited to, chloride salts, fluoride salts, carbonates, sulfates, and nitrates. In theory, any compound that can form a eutectic salt system with the alkali flux NaOH can be used as the auxiliary salt.
[0014] The ultrasound in step (3) is conventional water bath ultrasound, which plays a role in assisting dispersion. The ultrasound frequency is 40KHz and the input power is 200W.
[0015] In the present invention, the molar ratio of the alkali flux to the auxiliary salt is lower than 4-19:1. Firstly, the amount of the alkali flux NaOH will be insufficient, and secondly, the melting point of the mixture after mixing with the auxiliary salt is high, resulting in uneven reaction. If the molar ratio is higher than 4-19:1, the auxiliary salt accounts for a small proportion, and the eutectic salt is difficult to form uniformly.
[0016] In a specific embodiment of the present invention, in step (1), the lithium slag raw material needs to be sieved before the acid washing pretreatment so that the particle size of the lithium slag particles is ≤80 μm.
[0017] In a specific embodiment of the present invention, in step (1), during the pickling pretreatment, the acid is at least one of hydrochloric acid and sulfuric acid, and the acid concentration is 0.1-0.5 M; the pickling pretreatment is stirred at 20-60° C. for 0.5-3 h, followed by filtering, washing to neutrality, and drying to remove impurities.
[0018] In a specific embodiment of the present invention, in step (1), the pretreated lithium slag comprises the following components in mass parts: 30% to 80% SiO2, 10% to 40% Al2O3; except for SiO2 and Al2O3 components, the mass proportion of the remaining components in the pretreated lithium slag is ≤5%. Preferably: the pretreated lithium slag comprises the following components in mass parts: 50% to 75% SiO2, 20% to 35% Al2O3 3; Except for SiO2 and Al2O3 components, the mass proportion of other components in the pretreated lithium slag is ≤5%.
[0019] In a specific embodiment of the present invention, in step (2), the temperature during alkali melting is 200-320° C. and the time is 2-6 hours.
[0020] In a specific embodiment of the present invention, in step (2), the temperature during alkali fusion is 250-300°C and the time is 2-4 hours; preferably, the temperature during alkali fusion is 300°C and the time is 2 hours.
[0021] In a specific embodiment of the present invention, in step (2), the mass ratio of the pretreated lithium slag to the eutectic salt is 1:1-3; preferably, the mass ratio of the pretreated lithium slag to the eutectic salt is 1:2.2-2.5.
[0022] In a specific embodiment of the present invention, in step (3), the solid-liquid mass ratio during aging is 1:10-50; preferably, the solid-liquid mass ratio during aging is 1:20.
[0023] In a specific embodiment of the present invention, the molar ratio of the alkali flux to the auxiliary salt is 9-13:1.
[0024] In a specific embodiment of the present invention, the molar ratio of the alkali flux to the auxiliary salt is 13:1.
[0025] In a specific embodiment of the present invention, the auxiliary salt is at least one of sodium carbonate, sodium chloride and sodium sulfate.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) Acid pickling pretreatment can effectively remove impurities such as sulfur and calcium in lithium slag, increase the content of SiO2 and Al2O3, reduce the impact of impurities on the crystal growth process, and make the product have good uniformity.
[0028] (2) The eutectic salt system was introduced during the lithium slag alkali melting stage, which reduced the alkali melting temperature, promoted the reaction between lithium slag and alkali, increased the molecular sieve yield, and reduced energy consumption.
[0029] (3) The auxiliary salt in the eutectic salt has a positive effect on the formation of molecular sieves and can lead to the formation of specific molecular sieves. The anions and cations in the eutectic salt combine with silicon-aluminum oxides to promote particle dispersion and play a role in regulating the morphology of the molecular sieve.
[0030] (4) Without the need to add additional silicon or aluminum sources, the treated lithium slag can be used to prepare specific molecular sieves (such as NaX molecular sieves with a relative content ≥98% and NaP molecular sieves with a relative content ≥98%), thereby achieving high-value utilization of waste at low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The XRD diagrams of the products of Examples 1-5 and Comparative Examples 1-2 are shown;
[0032] Figure 2 and Figure 3This is the SEM image of lithium slag raw material (after passing through a 200-mesh sieve) and after pickling pretreatment;
[0033] Figure 4-Figure 8 They are SEM images of the products of Examples 1-5 respectively;
[0034] Figure 9-11 It is the SEM picture of the product of comparative example 1-3;
[0035] Fig.12 It is the XRD pattern of the product of Comparative Example 4;
[0036] Fig.13 This is the SEM image of the product of Comparative Example 4. DETAILED DESCRIPTION
[0037] The present invention is further described below with specific examples, but the embodiments of the present invention are not limited thereto.
[0038] The lithium slag raw materials used in the embodiments and comparative examples of the present invention and the components after pretreatment are shown in the following table.
[0039] Table 1 Composition of lithium slag raw materials and after pickling pretreatment
[0040] sample / % <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO <![CDATA[SO3]]> <![CDATA[Fe2O3]]> <![CDATA[Na2O]]> <![CDATA[K2O]]> MgO <![CDATA[P2O5]]> <![CDATA[Rb2O]]> raw material 59.12 25.33 5.16 7.54 1.07 0.55 0.44 0.13 0.29 0.11 Pickling 69.42 27.72 0.34 0.39 0.83 0.21 0.43 0.08 0.16 0.13
[0041] The steps of pickling pretreatment of lithium slag raw materials are as follows: the lithium slag raw materials are sieved through a 200-mesh sieve and pickled with 0.1M hydrochloric acid for pretreatment, stirred and reacted at 60°C for 2h, then filtered and washed to neutrality, and dried to remove impurities to obtain pretreated lithium slag.
[0042] Example 1
[0043] The pretreated lithium slag was mixed with the eutectic salt composed of NaOH and Na2CO3 in a mass ratio of 1:2.5, wherein the molar ratio of NaOH to Na2CO3 was 13:1, and the mixture was placed in a muffle furnace and heated at 300°C for 2h. Pure water was added to the calcined product in a mass ratio of 1:20, stirred at room temperature for 30min, ultrasonicated for 30min, and then the solution was transferred to a hydrothermal kettle for hydrothermal reaction at 120°C for 24h, cooled to room temperature, filtered, washed, and dried to obtain a molecular sieve.
[0044] Example 2
[0045] The pretreated lithium slag was mixed with the eutectic salt composed of NaOH and NaCl in a mass ratio of 1:2.2, wherein the molar ratio of NaOH to NaCl was 13:1, and the mixture was placed in a muffle furnace and heated at 300°C for 2h. Pure water in a mass ratio of 1:20 was added to the calcined product, stirred at room temperature for 30min, ultrasonicated for 30min, and then the solution was transferred to a hydrothermal kettle, hydrothermally reacted at 120°C for 24h, cooled to room temperature, filtered, washed, and dried to obtain a molecular sieve.
[0046] Example 3
[0047] The pretreated lithium slag was mixed with the eutectic salt composed of NaOH and NaCl in a mass ratio of 1:2.2, wherein the molar ratio of NaOH to NaCl was 13:1, and the mixture was placed in a muffle furnace and heated at 200°C for 6 hours. Pure water was added to the calcined product in a mass ratio of 1:20, stirred at room temperature for 30 minutes, ultrasonicated for 30 minutes, and then the solution was transferred to a hydrothermal kettle for hydrothermal reaction at 120°C for 24 hours. After cooling to room temperature, it was filtered, washed, and dried to obtain a molecular sieve.
[0048] Example 4
[0049] The pretreated lithium slag was mixed with the eutectic salt composed of NaOH and NaCl in a mass ratio of 1:1.05, wherein the molar ratio of NaOH to NaCl was 9:1, and the mixture was placed in a muffle furnace and heated at 350°C for 2h. Pure water in a mass ratio of 1:20 was added to the calcined product, stirred at room temperature for 30min, ultrasonicated for 30min, and then the solution was transferred to a hydrothermal kettle, hydrothermally reacted at 120°C for 24h, cooled to room temperature, filtered, washed, and dried to obtain a molecular sieve.
[0050] Example 5
[0051] The pretreated lithium slag was mixed with the eutectic salt composed of NaOH and Na2SO4 in a mass ratio of 1:2.5, wherein the molar ratio of NaOH to Na2SO4 was 13:1, and the mixture was placed in a muffle furnace and heated at 300°C for 2h. Pure water in a mass ratio of 1:20 was added to the calcined product, stirred at room temperature for 30min, ultrasonicated for 30min, and then the solution was transferred to a hydrothermal kettle, hydrothermally reacted at 120°C for 24h, cooled to room temperature, filtered, washed, and dried to obtain a molecular sieve.
[0052] Comparative Example 1
[0053] The pretreated lithium slag was mixed with a eutectic salt composed of NaOH and NaCl in a mass ratio of 1:2.2, wherein the molar ratio of NaOH to NaCl was 13:1, and pure water in a mass ratio of 1:20 was directly added. After stirring and reacting at room temperature for 30 minutes, ultrasonication was performed for 30 minutes, and then the solution was transferred to a hydrothermal kettle and hydrothermally reacted at 120°C for 24 hours. After cooling to room temperature, the product was filtered, washed, and dried.
[0054] Comparative Example 2
[0055] The pretreated lithium slag was mixed with NaOH in a mass ratio of 1:2 and the mixture was placed in a muffle furnace and heated at 300°C for 2h. Pure water in a mass ratio of 1:20 was added to the calcined product, stirred at room temperature for 30min, ultrasonicated for 30min, and then the solution was transferred to a hydrothermal kettle for hydrothermal reaction at 120°C for 24h. After cooling to room temperature, the molecular sieve was filtered, washed, and dried.
[0056] Comparative Example 3
[0057] The pretreated lithium slag was mixed with the eutectic salt composed of NaOH and Na2CO3 in a mass ratio of 1:2.5, wherein the molar ratio of NaOH to Na2CO3 was 3:1, and the mixture was placed in a muffle furnace and heated at 300°C for 2h. Pure water in a mass ratio of 1:20 was added to the calcined product, stirred at room temperature for 30min, ultrasonicated for 30min, and then the solution was transferred to a hydrothermal kettle, hydrothermally reacted at 120°C for 24h, cooled to room temperature, filtered, washed, and dried to obtain a molecular sieve.
[0058] Comparative Example 4
[0059] The pretreated lithium slag and NaOH were mixed and ground in a mass ratio of 1:2, and pure water was added in a mass ratio of 1:50. The mixture was stirred and reacted at room temperature for 30 minutes, and ultrasonicated for 30 minutes. The solution was then transferred to a hydrothermal kettle and hydrothermally reacted at 120°C for 24 hours. After cooling to room temperature, the product was filtered, washed, and dried.
[0060] The X-ray diffraction patterns of the molecular sieves prepared in Examples 1-5 and Comparative Examples 1-2 are shown in Figure 1 SEM images of lithium slag raw material (after passing through a 200 mesh sieve), lithium slag after acid washing pretreatment, and molecular sieves prepared in Examples 1-5 and Comparative Examples 1-3 are shown in FIG. Figure 2-11 The X-ray diffraction pattern of the molecular sieve prepared in Comparative Example 4 is shown in Fig.12 As shown; the SEM image of the molecular sieve prepared in Comparative Example 4 is shown Fig.13 shown.
[0061] Example 1 is a eutectic salt system composed of NaOH and Na2CO3. Through the melting and hydrothermal crystallization process, the product obtained is a NaP type molecular sieve (Na6Al6Si 10 O 32 ) and 2% SiO2; Figure 4 It can be observed that the product is well dispersed. Except for large particles, the particle size of the surrounding dispersed particles is significantly reduced. This shows that the addition of Na2CO3 promotes the decomposition and reconstruction of lithium slag raw materials and plays a regulatory role in the morphology of the generated molecular sieve. Example 2 is a eutectic salt system composed of NaOH and NaCl. Through the melting and hydrothermal crystallization process, the product obtained is a NaX type molecular sieve (Na 92 (Si 100 Al 92 O 384 )) and a small amount of NaP type molecular sieve; from Figure 5 It can be observed that the product morphology is uniform and has good homogeneity. From Examples 1 and 2, it can be seen that auxiliary salts can regulate the morphology of molecular sieves. Specifically, the morphology of molecular sieve particles guided by carbonate and chloride salts is obviously different. The product obtained in Example 3 is a molecular sieve with a relative content of 52% NaX and 48% NaP; Figure 6 The corresponding electron microscope image shows a mixture of two particles with different morphologies, which indicates that the single molecular sieve generated by the eutectic salt system requires a specific range of melting temperature and time conditions. The product obtained in Example 4 is a mixture of 60% NaX type molecular sieve and 20% NaA type (Na 96 Al 96 Si 96 O 384 , regular dodecahedron) and a small amount of NaP, SiO2 mixture. The product of Example 4 contains more SiO2, mainly because the amount of NaOH used is reduced, thereby reducing the reactants with lithium slag, affecting the generation of active ingredients and the crystallization process of molecular sieves, resulting in an increase in the content of partial silicon oxide. Figure 7 Mixed products can be observed in the corresponding electron microscope images, which shows that different amounts of reactants can affect the type of molecular sieve formed. Example 5 is a eutectic salt system composed of NaOH and Na2SO4, and the obtained product is a pure NaP type molecular sieve with a relative content of more than 99%; Figure 8 Evenly dispersed molecular sieve particles can be observed in the
[0062] Comparative Example 1 is a eutectic salt system composed of NaOH and NaCl, which is directly subjected to hydrothermal reaction without melting. Comparative Example 2 does not add auxiliary salt and alkali flux to form a eutectic salt, but directly undergoes alkali melting and then hydrothermal crystallization. The product obtained in Comparative Example 1 is a mixture of NaP type molecular sieve and SiO2, wherein the relative content of NaP type molecular sieve is 86%, and the relative content of SiO2 is 14%, indicating that some raw materials are still unreacted. It also means that the auxiliary salt "guiding the formation of a specific molecular sieve" requires specific reaction conditions, and adding chloride salts does not necessarily generate NaX type. Without calcination, the auxiliary salt has limited effect, and the lithium slag can only partially react in the alkaline solution. The silicon-aluminum active material generated by the reaction generates part of the NaP type molecular sieve. Correspondingly, from Fig. 9 It can also be observed that there are many unreacted lithium slag fragments in the product. The main reason why there is no agglomeration in Comparative Example 1 is that it has not been calcined, and the raw material particles themselves have a certain degree of dispersibility in the aqueous solution; secondly, the added auxiliary salt plays a role in regulating the morphology, making the generated molecular sieve particle size uniform. The product of Comparative Example 2 is a mixture of NaP type with a relative content of 38%, NaX type with a relative content of 16%, and silicon oxide with a relative content of 46%. Corresponding Fig.10 It can be found that the product of Comparative Example 2 is seriously agglomerated. This is because the melting point of sodium hydroxide is 318.4°C. At a temperature of 300°C, part of the solid phase will transform into the liquid phase, but the phase change is incomplete, resulting in insufficient reaction contact surface. After the reaction temperature drops, part of the reacted and unreacted lithium slag particles are agglomerated together during the liquid-solid transformation process, resulting in serious agglomeration. In addition, the silicon-aluminum ratio is unbalanced, affecting the subsequent hydrothermal crystallization process, resulting in the presence of a large amount of silicon oxide. Comparative Example 3 is the product obtained when the molar ratio is 3:1, corresponding to Fig.11 It can be found that no molecular sieve with regular morphology is generated, the product is severely agglomerated, and unreacted lithium slag particles are clearly present. This is because NaOH and the auxiliary salt need to form a eutectic salt in a specific molar ratio. If the molar ratio is too low, it will cause insufficient use of the alkaline flux NaOH, and secondly, the melting point of the mixture after mixing with the auxiliary salt is high, resulting in uneven reaction. The product obtained in Comparative Example 4 is a mixture of NaP molecular sieve and SiO2, in which the relative content of NaP molecular sieve is 87%, and the relative content of SiO2 is 13%, indicating that some raw materials are still unreacted; the corresponding Fig.13 It can also be observed that in Comparative Example 4, although the lithium slag can self-assemble into balls through hydrothermal reaction in an alkaline solution, there are many unreacted lithium slag fragments in the product.
[0063] By comparison, it can be seen that the eutectic salt system helps to disperse the particles and promotes the reaction between alkali and lithium slag; the type of auxiliary salt in the eutectic salt, the proportion of each component, the calcination temperature, etc. have a key influence on the formation of molecular sieves. Comparing Example 1, Example 2 and Comparative Example 2, carbonates and chlorides lead to the formation of NaP-type and NaX-type molecular sieves, respectively, and the addition of the eutectic salt system has a regulatory effect on the particle morphology. Compared with Example 1, the low-temperature calcination process can promote the melting reaction and make the lithium slag react to generate more effective compounds. Examples 2-4 illustrate that the formation of molecular sieves changes with the proportion of eutectic salt components, calcination temperature and time. Compared with Comparative Example 1 and Comparative Example 4, the addition of sodium chloride when preparing molecular sieves from lithium slag can adjust the morphology of the molecular sieve, and the molecular sieve particle size is smaller and the molecular sieve specific surface area is larger.
[0064] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention still fall within the scope covered by the present invention.
Claims
1. A method for preparing lithium slag-based molecular sieves by eutectic salt-assisted melting of lithium slag, characterized in that: The following steps are involved: (1) pickling pretreatment: the lithium slag raw material is subjected to pickling pretreatment to obtain pretreated lithium slag; (2) Alkali melting: The pretreated lithium slag is ground and mixed with eutectic salt, and reacted at 250-300°C for 2-4 hours to obtain eutectic lithium slag; (3) Ripening: adding the eutectic lithium slag into water, stirring for 0.5 to 2 hours, and then ultrasonicating for 0.5 to 1 hour to obtain a mixed solution containing silicon-aluminum compounds; (4) Crystallization: crystallizing the mixed solution containing silicon-aluminum compounds at 80-140° C. for 6-24 hours, separating the solid and the liquid after the reaction, washing the solid to neutrality, and drying to obtain a lithium slag-based molecular sieve; The eutectic salt includes an alkali flux and an auxiliary salt, the alkali flux is sodium hydroxide, and the auxiliary salt is at least one of chloride salt, fluoride salt, carbonate, sulfate, and nitrate; the molar ratio of the alkali flux to the auxiliary salt is 4 to 19:1; In step (2), the mass ratio of the pretreated lithium slag to the eutectic salt is 1:2.2-2.
5.
2. The method for preparing lithium slag-based molecular sieve by eutectic salt-assisted melting of lithium slag according to claim 1, characterized in that: In step (1), the lithium slag raw material needs to be screened before the pickling pretreatment so that the particle size of the lithium slag particles is ≤80 μm.
3. The method for preparing lithium slag-based molecular sieve by eutectic salt-assisted melting of lithium slag according to claim 1, characterized in that: In step (1), during the pickling pretreatment, the acid is at least one of hydrochloric acid and sulfuric acid, and the acid concentration is 0.1 to 0.5 M; the pickling pretreatment is stirred at 20 to 60° C. for 0.5 to 3 hours, followed by filtering, washing to neutrality, and drying to remove impurities.
4. The method for preparing lithium slag-based molecular sieve by eutectic salt-assisted melting of lithium slag according to claim 1, characterized in that: In step (1), the pretreated lithium slag includes the following components in parts by weight: 30% to 80% SiO2, 10% to 40% Al2O3; except for SiO2 and Al2O3 components, the mass proportion of the remaining components in the pretreated lithium slag is ≤5%.
5. The method for preparing lithium slag-based molecular sieve by eutectic salt-assisted melting of lithium slag according to claim 1, characterized in that: In step (3), the solid-liquid mass ratio during aging is 1:10 to 50.
6. The method for preparing lithium slag-based molecular sieve by eutectic salt-assisted melting of lithium slag according to claim 1, characterized in that: The molar ratio of the alkali flux to the auxiliary salt is 9 to 13:
1.
7. The method for preparing lithium slag-based molecular sieve by eutectic salt-assisted melting of lithium slag according to claim 1, characterized in that: The molar ratio of the alkali flux to the auxiliary salt is 13:
1.
8. The method for preparing lithium slag-based molecular sieve by eutectic salt-assisted melting of lithium slag according to claim 1, characterized in that: The auxiliary salt is at least one of sodium carbonate, sodium chloride and sodium sulfate.
Citation Information
Patent Citations
Method for preparing 13 X molecular sieve by using lithium slag as raw materials
CN101624191A
A Low-Temperature Preparation Method of Lithium Slag-Based NaA Molecular Sieves
CN109485062B
Green preparation method of CuY molecular sieve for adsorption desulfurization
CN110759354A
Method for preparing molecular sieve from lithium slag
CN113548673A
Method for preparing magnetic zeolite adsorbent from alkaline lithium slag, magnetic zeolite adsorbent and application
CN117920132A